TEACHING PRONUNCIATION PRACTICE BY USING GOOGLE CLASSROOM TO THE SECOND SEMESTER STUDENTS OF ENGLISH TADRIS STUDY PROGRAM AT STATE INSTITUTE FOR ISLAMIC STUDIES PALU - afifah (Datokarama English Education Journal, 2021)
This is a qualitative research with the objective to find out how the teaching of Pronunciation Practice by using Google Classroom to the second semester students of English Tadris Study Program of State Institute for Islamic Studies (IAIN) Palu is. There are three research questions in this research: (1) How did the lecturer teach Pronunciation Practice subject by using Google Classroom to the second semester students of English Tadris Study Program of State Institute for Islamic Studies Palu ?; (2) What are the advantages and limitations of using Google Classroom for teaching Pronunciation Practice to the second semester students of English Tadris Study Program of State Institute for Islamic Studies Palu?; and (3) What are the advantages and limitations of using Google Classroom for learning Pronunciation Practice based on the opinions of the second semester students of English Tadris Study Program of State Institute for Islamic Studies Palu? In gaining the date, the researcher used observation and interview as the instruments. From the observation, the researcher answered the first and second research questions as follow. The researcher did several steps in teaching Pronunciation Practice by using Google Classroom such as: (1) making three classes of Pronunciation Practice in Google Classroom for TBIG-1, TBIG-2, and TBIG-3; (2) sharing the link of Google Classroom to the students; (3) making the attendance list; (4) delivering the material to the students by attaching word files; (5) sharing YouTube videos of how native speaker pronouncing the sounds in the material; (6) giving assignment to the students by setting the deadline; and (7) returning the assignment to the students along with the score and the feedback in the comment column. The advantages by using Google Classroom for teaching Pronunciation Practice are as follow: (1) the easiness to deliver the material orderly; (2) the easiness to share YouTube videos; (3) the easiness to instruct an assignment; (4) the easiness to set the due date of the assignment; (5) the availability of scoring feature; (6) the privacy of lecturer’s feedback; and (7) no need to save students’ numbers. However, the limitations of Google Classroom are also found. Here are some of the limitations: (1) the unavailability of attendance feature; (2) the need of stable internet connection to upload a material file; and (3) the unavailability of feature to do oral class discussion. The third research question was answered by using the data from interview. The students described the advantages of using Google Classroom as follow: (1) easy to use; (2) flexible; (3) easy to send tasks; (4) not consuming much internet data; and (5) enabling students to watch YouTube videos shared by the lecturer related to the material discussed. However, they also noted some limitations of Google Classroom such as: (1) the unavailability of features like voice note and video call to have oral class discussion; (2) the difficulty to access it when the internet connection is not stable; and (3) the difficulty to send tasks when Google Drive is full.